2019
DOI: 10.3960/jslrt.19028
|View full text |Cite
|
Sign up to set email alerts
|

Immune response in LPD during methotrexate administration (MTX-LPD) in rheumatoid arthritis patients

Abstract: Methotrexate (MTX) is known as a first-line synthetic disease-modifying anti-rheumatic drug (DMARD) for the treatment of rheumatoid arthritis (RA). Although the risk of LPD development increases by RA inflammation itself, observation of spontaneous regression of LPD after MTX discontinuation lead to the theory of lymphomagenic role of MTX. In this review, we focused on the several immune response involved in LPD that developed under MTX administration in RA patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 101 publications
(101 reference statements)
1
14
0
Order By: Relevance
“…Other frequent subtypes are reactive lymphoid hyperplasia, classic Hodgkin lymphoma, polymorphic B cell LPD, and indolent lymphoma which includes follicular lymphoma [ 21 ]. Some studies have shown that patients who are EBV-positive and non-DLBCL histological type have a high prevalence of spontaneous remission [ 22 ]. EBV-positive DLBCL is categorized as polymorphous lymphoma and large cell lymphoma subtypes, and a number of previous reports have revealed that the polymorphous lymphoma has a good prognosis than large cell lymphoma [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other frequent subtypes are reactive lymphoid hyperplasia, classic Hodgkin lymphoma, polymorphic B cell LPD, and indolent lymphoma which includes follicular lymphoma [ 21 ]. Some studies have shown that patients who are EBV-positive and non-DLBCL histological type have a high prevalence of spontaneous remission [ 22 ]. EBV-positive DLBCL is categorized as polymorphous lymphoma and large cell lymphoma subtypes, and a number of previous reports have revealed that the polymorphous lymphoma has a good prognosis than large cell lymphoma [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported that EBVMCU develops as Oii-LPD induced by MTX treatment, and nearly all EBVMCU cases showed a favorable response to conservative management approaches such as the cessation of the MTX treatment for RA [ 25 ]. Although the detection rate of EBV is 5–10% in canonical LPD, the rate increases to 27% and 30–60% in patients with MTX-LPD and rheumatoid arthritis-associated LPD, respectively [ 18 , 22 ]. Among RA patients with EBV-positive MTX-LPD, a lower incidence of DNA methylation in tumors and higher expression of tumor suppressor genes were observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in recent years, the number of cases reporting MTX‐associated lymphoproliferative disorders (MTX‐LPD) has increased rapidly in Japan. 1 , 2 , 3 , 4 , 5 , 6 MTX‐LPD is also classified as “other iatrogenic immunodeficiency‐associated lymphoproliferative disorder” in the 4th edition of the World Health Organization classification. 7 However, it is difficult to determine whether MTX‐LPD is caused by the autoimmune disease or the treatment with immunosuppressive drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Lymphoproliferative disorder (LPD), including malignant lymphoma, is a rare but life-threatening complication in patients with RA ( 2 , 3 ). The risk of LPD is higher in RA patients than in the general population ( 4 , 5 ), and based on reports on the regression of LPD after MTX cessation ( 6 ), LPD has been considered to occur during the suppression of immune surveillance with MTX administration ( 3 ). LPD that developed under the administration of immunosuppressive agents was categorized as ‘other-iatrogenic immunodeficiency-associated LPD’ in the 2008 World Health Organization classification of tumors or hematopoietic and lymphoid tissues ( 7 ).…”
Section: Introductionmentioning
confidence: 99%